Pattern of deaths in females in a tertiary health center, south-west Nigeria - Omoniyi-Esan GO; Olaofe OO; Onwubuya MI; Fadahunsi OO; Komolafe AO (Dove Medical Press, 2011)
Olutoyin Omoniyi-Esan1, Olaejirinde Olaofe2, Mary Onwubuya2, Oluseyi Fadahunsi2, Akinwumi Komolafe11Department of Morbid Anatomy and Forensic Medicine, College of Health Sciences, Obafemi Awolowo University, 2Departments of Morbid Anatomy and Forensic Medicine, Obafemi Awolowo University Teaching Hospital, Ile-Ife, Osun State, NigeriaPurpose: The aim of this study was to review autopsies to determine the pattern of deaths in females at Wesley Guild Hospital, Ilesa, Nigeria.Methods: A 9-year retrospective study was done of all autopsies done on females in the Department of Morbid Anatomy and Forensic Medicine, Obafemi Awolowo University Teaching Hospitals Complex, Wesley Guild Hospital, Ilesa, Nigeria, from January 2002 to December 2010. Records of all autopsies done on females during the period were reviewed.Results: During the study period 215 cases of female death were autopsied. The age range was 0-75 years (mean = 32.9). Deaths due to trauma were most common (57.2%), followed by obstetric deaths (15.8%). Deaths due to infections and cardiovascular diseases accounted for 13% and 5.6%, respectively. Injuries sustained from automobile accidents were responsible for 88.6% of all trauma deaths. Gunshot injuries accounted was 4.9% of these trauma deaths. The causes of death from automobile accidents included multiple injuries (49.5%), head injury (38.5%), and hypovolemia (8.3%). Obstetric deaths were predominantly due to uterine sepsis (51.5%) and hemorrhagic shock (39.4%). About 39% of deaths from infection were due to septicemia. Acute bacterial meningitis, acute lobar pneumonia, and malaria caused 23.1%, 15.4%, and 7.7% of deaths from infections, respectively. Four cases of sudden unnatural deaths (other than trauma) were recorded.Conclusion: Trauma was the most common cause of death in women autopsied in our hospital, and automobile injuries were the most common causes of these trauma deaths. Obstetric deaths ranked second. Sepsis and hemorrhage were the most common causes of these obstetric deaths. Deaths from eclampsia were low. Requests for autopsies on women who died from cancer were few. There is a need for clinicians to ascertain the actual cause of death in women who die from cancer.Keywords: females, mortality, autopsy